METHOD OF DETERMINING THE PARAMETERS OF THE WAVE-LIKE SURFACE WEAR ON RAILS ROLLING IN ACCORDANCE WITH CORRELATION FUNCTION - Levochko, B. S.; Makhota, A. O.; Shekhvatov, O. O. (Science and Transport Progress, 2003)
A waveform wear, nascent on rails during their exploitation, is described by successive alternation of smooth geometrical roughness of three groups – short, middle and long. The two component model of waveform wears and methods of depth and length determination of roughness are offered. The methods we the principles of correlation analysis within the offered model.